Children's Theater: A Paradigm, Primer, and Resource - Eggers, Kelly; Eggers, Walter (Rowman & Littlefield Publishers, 2010)
Although there are many children's theater companies located around the world, more parents and educators need to know what a significant impact such venues can have on the lives of their participants. For anyone interested in learning more about these creative outlets, Children's Theater: A Paradigm, Primer, and Resource serves several purposes. First, this book introduces readers to the world of children's theater by highlighting one specific model, The Oyster River Players, a small children's theater company in New Hampshire. By exploring the history and dynamics of their own theater company, authors Kelly and Walter Eggers apply broader implications, expanding their focus to include children's theaters of other kinds and in different cultural settings. Throughout the book, the Eggers show how children's theater succeeds in helping young people learn in ways that would be otherwise inaccessible. Through forays into philosophy and history, as well as personal testimonies, the authors present a coherent argument for the need for children's theaters in nearly every community. This volume also lists more than 600 children's theater companies, agencies, and associations in the United States, as well as 400 more worldwide. Both accessible and practical, Children's Theater is an essential tool for teachers, directors, parents, mentors, and anyone else involved or interested in children's theater and its implications for children's education.